Influence of awakening from general anesthesia on the distribution of glucose 2.5% with balanced electrolytes in adults - Hahn, Robert G.; Sjöstrand, Fredrik (Frontiers in Medicine, 2025)
BackgroundThe glucose-free crystalloid fluid used for intravenous infusion during surgery might be combined with or replaced by 2.5% glucose in debilitated patients. The aim of the present study was to use kinetic modeling to quantify the distribution of 2.5% glucose with balanced electrolytes administered during and after general anesthesia. The hypothesis was that awakening from anesthesia changes glucose and/or fluid volume kinetics in distinct ways.MethodsA secondary analysis was performed based on data derived during and after intravenous administration of an isotonic mixture of 20 mL/kg of glucose 2.5% with electrolytes over 60 min in 12 non-diabetic adult patients undergoing laparoscopic cholecystectomy. Population glucose and volume kinetic analyses were performed based on blood and urine data collected for 4 h, which included 2 postoperative hours. Periods before and after awakening from anesthesia were contrasted using covariate analysis and further compared to 35 infusions in 17 awake volunteers who had received the same fluid at different rates and volumes.ResultsThe return flow of distributed fluid to the plasma was strongly retarded during and after anesthesia and promoted peripheral edema. Awakening decreased the rate of distribution, which counteracted the additional build-up of this edema but expanded the plasma volume. Urine output was strongly dependent on the mean arterial pressure; the urine flow rate at 75 mmHg was only 22% of the flow rate obtained at 90 mmHg. Simulations showed that the rate of administration of glucose 2.5% should be < 500 mL over 30 min to maintain plasma glucose < 10 mmol/L during surgery and postoperatively.ConclusionAwakening from general anesthesia inhibits the distribution of 2.5% glucose solution and accelerates the return of distributed fluid, with both responses increasing the plasma volume. These two effects counteract postoperative development of hypovolemia.